Synthesis of zeolitic imidazolate framework-8 (ZIF-8) using N,N-dimethylformamide as solvent - Chun, Yong Yao. (2012)
One of the subclass of metal organic frameworks (MOFs), Zeolitic imidazolate frameworks (ZIFs), like other microporous materials exhibit large surface and pores volume, which make ZIF materials useful in gas storage application. Besides, ZIFs also exhibit high thermal and chemical stability, which are suitable for extreme operational conditions of industrial chemical processes. However, it is still a challenge to tailor the shape and size of ZIFs to match for specific application.